Histórias cruzadas: mazelas do Brasil na obra de Graciliano Ramos (em diálogo com a filosofia de Theodor Adorno) - Freire, Pedro Antônio (2015)
This study recognizes the importance of the work of two of the most important thinkers of the twentieth century by relating Brazilian novelist Graciliano Ramos" and the German philosopher Theodor Adorno" works. The former, in the archaic and mystical Alagoas hinterland, and the latter, in the sophisticated and idealistic Frankfurt, both started out their careers before the Second World War and, despite the quite different contexts, both suffered serious consequences due to their posture. The author of Vidas secas (Barren Lives) was raised in an extremely punitive household due to his parents" socioeconomic condition and religious views. As an adult he bore fascist persecution that resulted in his imprisonment during the dictatorship of Getúlio Vargas. The German-Jewish carried out a permanent toil against Hitler"s National Socialism since his early academic preparation and later with the foundation of the Institute for Social Research in Frankfurt, a decision that forced him into exile. After the war was over, he resumed his considerations in opposition to the capitalist system and Regimes of Exception. As for Graciliano, his time in prison prompted him to elaborate narratives drawn from his own mishaps and problems of Brazilian society. The fact is that both, each in their own way, made their works vehicles of criticism and contestation of established powers and values. This dissertation aims to articulate a "cross-history", bringing up the discussion of some concepts – such as grief and gloom, disaster and trauma, atheism, non-identical, art and work, literature and nationalism, language and society – that are a constant presence in theirs books, which, in short, interpret the world as a permanent catastrophe.